Ethical Issues in Humanitarian Work: Perceptions of Humanitarian Ethics Experts, Workers, and Non-Governmental Organization Members - Valgimigli, Federico; Côté, Louis; Drolet, Marie-Josée (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
This study aims to empirically document the perceptions and experiences of diverse humanitarian actors, including humanitarian workers, NGO members, and humanitarian ethics experts, regarding ethical issues in humanitarian work. We conducted 15 interviews with participants, from which we extracted four categories of ethical issues: value-based tensions, resource scarcity, political considerations, and neocolonialism. The category of value-based tensions encompasses ethical issues involving intercultural conflicts, balancing care with security and collaboration, addressing emergency versus long-term care, and navigating ethical silence. Resource scarcity includes issues such as a lack of financial and material resources, insufficient preparation, and inadequate ethical resources, all of which contributing to operational difficulties. The category of political considerations highlights ethical issues related to NGO operations, including the disconnect between organizational decisions and field practices, the unequal treatment of local workers and expatriates, and instances of authoritarianism, racism, and corruption within NGOs and their partners. Ethical issues pertaining to neocolonialism highlights how Western ideologies and power dynamics persist in humanitarian organizations, manifesting in issues like paternalism, control of decision-making by white individuals, and power imbalances between NGOs and local governments, perpetuating a sense of Western superiority over non-white individuals. As well, having identified ethical silence and neocolonialism as key ethical issues in this study (i.e., undiscussed in prior empirical literature reviewed), we propose a reflection on structural injustices and the systemic inequities in humanitarian work.